Pengaruh Communication Skill, Disiplin Kerja Dan Kualitas Sumber Daya Manusia Terhadap Kinerja Karyawan PDAM Cabang Banyuanyar Kabupaten Probolinggo - Muhammad Saifudin; Budi Wahono; Khalikussabir Khalikussabir (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract  This study aims to determine the effect of Communication Skill, Work Discipline and Quality of Human Resources on Employee Performance. The location of this research was carried out at the PDAM Banyuanyar Branch Office, Probolinggo Regency. This research is a quantitative study. This study uses a case study method where data is obtained by downloading employee performance reports at the PDAM Banyuanyar Branch Office, Probolinggo Regency. The sampling technique in this study used . Total sampling technique, which is a sampling technique where all members of the population are sampled as all subjects studied or as respondents providing information. The data analysis method in this study is using descriptive inferential statistical analysis using the SPSS assistance program which is used to analyze the data that has been obtained. through the answers to the questionnaire (questionnaire), the results of the F test indicate that the variables of communication skills, work discipline and the quality of human resources have a significant effect simultaneously or jointly on the performance of the employees of PDAM Banyuanyar Branch, Probolinggo Regency. Furthermore, the results of the t test show that communication skills, work performance and the quality of human resources have a partially significant effect on employee performance. Based on the results of this study indicate that communication skills between employees need to be improved and paid attention to in order to increase their performance to the maximum, then employee work discipline is good and needs to be maintained because employees can work on time, comply with existing regulations and hard workers need to be maintained in order to improve performance. maximally, and the quality of human resources that need to be improved in understanding more deeply related to tasks and making use of each, increasing knowledge and ability to work  Keywords: Communication Skill, Work Discipline, Quality Of Human Resources, Employee Performance